Puerperal sub-acute uterine inversion: a rare case report - Sharma, Reena; Malhotra, Kapil; Dogra, Poojan; Kumar, Anil; Kaushal, Sushruti; Priya, Tanu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Puerperal uterine inversion is a complication of third stage of labour, which can lead to maternal morbidity and mortality due to haemorrhage shock and infection. Early cases can be managed by manual reposition of uterus but neglected or late cases of uterine inversion are managed by Haultain`s repair. Here we are presenting a case of subacute uterine inversion referred from peripheral hospital managed by Haultain’s technique.